Time Resolution of the 4H-SiC PIN Detector - Yang, Tao; Tan, Yuhang; Liu, Qing; Xiao, Suyu; Liu, Kai; Zhang, Jianyong; Kiuchi, Ryuta; Zhao, Mei; Zhang, Xiyuan; Wang, Congcong; Wu, Boyue; Lin, Jianing; et al. (Frontiers in Physics, 2022)
We report the time resolution of 100um 4H-SiC PIN detectors which are fabricated by Nanjing University (NJU). The time responses for β particle from Sr-90 source are investigated for the detection of the minimum ionizing particles (MIPs). The influences of different reverse voltages which correspond to carrier velocity and device sizes which correlate with capacitance for time resolution are studied. We acquired a time resolution (94 +-1) ps for 100 um 4H-SiC PIN detector. A fast simulation software - RASER (RAdiation SEmiconductoR) has been developed to simulate the time resolution of 4H-SiC detector, and the simulation has been validated by the waveform comparison of RASER simulation and measured data. The simulated time resolution is (53 +- 1) ps after consider the intrinsic leading contributions of detector in time resolution.